Amorphous Transition Metal Sulfides Anchored on Amorphous Carbon‐Coated Multiwalled Carbon Nanotubes for Enhanced Lithium‐Ion Storage. Issue 56 (6th September 2017) - Jin, Rencheng; Zhai, Qinghe; Wang, Qingyao
Abstract: Cobalt sulfide and molybdenum sulfide, with high theoretical capacities, have been considered as one of most promising anode materials for lithium‐ion batteries (LIBs). However, the poor cyclability and low rate performances originating from the large volume expansion and poor electrical conductivity extremely inhibit their practical application. Here, the electrochemical performances are effectively improved by growing amorphous cobalt sulfide and molybdenum sulfide onto amorphous carbon‐coated multiwalled carbon nanotubes (CNTs@C@CoS2 and CNTs@C@MoS2 ). The CNTs@C@CoS2 presents a high reversible specific capacity of 1252 mAh g −1 at 0.2 Ag −1, excellent rate performance of 672 mAh g −1 (5 Ag −1 ), and enhanced cycle life of 598 mAh g −1 after 500 cycles at 2 Ag −1 . For CNTs@C@MoS2, it exhibits a specific capacity of 1395 mAh g −1, superior rate performance of 727 mAh g −1 at 5 Ag −1, and long cycle stability (796 mAh g −1 after 500 cycles at 2 Ag −1 ). The enhanced electrochemical properties of the electrodes are probably ascribed to their amorphous nature, the combination of CNTs@C that adhered and hindered the agglomeration of CoS2 and MoS2 as well as the enhanced electronic conductivity. Abstract : Hybrid power : Amorphous metal sulfides, anchored on carbon‐coated carbon nanotubes, are designed and fabricated through a facile and effective procedure. Such amorphous structures of CoS2 and MoS2, adhered to CNTs@C, which hinders the agglomeration of CoS2 and MoS2, are beneficial for improving the electrochemical performance of the electrodes.